Respuesta :

so this answer to this equation i got this:

x^2+x-12=0
x^2+4x-3x-12=0
x(x+4)-3(x+4)=0
(x-3)(x+4)=0

so (x-3)(x+4)=0 should be the answer

Hope this helped :)
Have a great day 

Answer:

[tex](x+4)(x-3)=0[/tex]

Step-by-step explanation:

A general expanded form of a quadratic equation could be write as follws:

[tex]ax^{2} +bx+c=0[/tex]

On the other hand, factored form equation could be generally write as:

[tex](x+q)(x+p)[/tex]

Where the parameters q and p are called the roots of the function.

1. In the case [tex]x^{2} +x-12=0[/tex], and taking into account the above, a = 1, b = 1 and c = - 12; and we need to find q an p.

2. Form the two factors taking into account the operation signs.

[tex](x+ p)(x-q)=0[/tex]

Note that in the first factor the sign of p is '+' because of the multiplication between the sign 'a (+)' and 'b (+)', then [tex]+ * + = +[/tex].  

In the same way, for the second factor the sign of q is '-' becasuse of the multiplication between the sign of 'b (+)' and 'c (-)', then [tex]+ * - = -[/tex].

3. As a=1, if you want to write a factored form you only need to find two numbers (p and q) whose multiplication is equal to -12, and whose sum is equal to +1.

By trial and error method you could determine that p=4 and q =-3 due to:

[tex]p*q=12\\(4)*(-3)=12\\p+q=1\\(4)+(-3)=1\\[/tex]

4. Locate the results of p and q in the two factors form:

[tex](x+ p)(x-q)=0\\(x+4)(x-3)=0[/tex]

This is the factored form of the quadratic equation [tex]x^{2} +x-12=0[/tex]

ACCESS MORE